Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as well as preparation method and application thereof
By preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel materials, and utilizing the self-propagating combustion and high-temperature reduction of glycine to form a three-dimensional network structure, combined with Mn doping for electromagnetic parameter control, the problems of high density, large thickness, and low low-frequency absorption efficiency of alloy absorbing materials were solved, achieving lightweight and efficient electromagnetic wave absorption performance, suitable for aerospace and flexible electronics fields.
Patent Information
- Application Number
- CN202511731080.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-24
- Publication Date
- 2026-02-06
AI Technical Summary
Existing alloy absorbing materials have high density, large thickness, and low low-frequency absorption efficiency, making it difficult to meet the needs of aerospace and flexible electronics for lightweight and thin-layer materials. Furthermore, traditional aerogel materials have limited absorption performance in the low-frequency band.
A method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel materials was adopted. The porous structure was formed by the self-propagating combustion of glycine, and the alloy nanoparticles were connected to form a three-dimensional network structure during high-temperature reduction. Electromagnetic parameters were controlled and impedance matching was optimized by combining Mn doping.
It achieves lightweight and efficient electromagnetic wave absorption performance, significantly enhancing the absorption capacity and effective absorption bandwidth in the low-frequency band, and is suitable for fields such as electromagnetic shielding and radar stealth.
Smart Images

Figure CN121466935A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, and more specifically, to a Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, its preparation method, and its application. Background Technology
[0002] With the rapid development of electronic communication technology, there is an urgent need for electromagnetic wave absorbing materials in complex electromagnetic environments, especially in low-frequency bands (such as communication and electronic equipment). Traditional absorbing materials mostly focus on mid-to-high frequencies and are difficult to achieve effective, full-band coverage in low frequencies, resulting in prominent low-frequency electromagnetic interference and leakage problems, which threaten the normal operation of equipment and information security. Therefore, it is of great significance to develop lightweight materials that are suitable for low-frequency and full-band absorption.
[0003] In existing technologies, alloy-based microwave absorbing materials exhibit certain absorption advantages in the low-frequency band, attenuating electromagnetic waves through their own magnetic and electrical properties. However, due to the inherent high density of the alloy and the influence of the manufacturing process, the finished products are thick and heavy, making it difficult to meet the needs of aerospace, flexible electronics, and other fields for "lightweight and thin-layer" microwave absorbing protection. Aerogel materials, on the other hand, possess lightweight and porous characteristics, showing significant potential for lightweight applications. However, the microwave absorbing performance of aerogels alone is limited, especially in the low-frequency band where they are difficult to absorb effectively. Summary of the Invention
[0004] The problem that this invention aims to solve is that existing alloy absorbing materials have high density, large thickness, and low low-frequency absorption efficiency.
[0005] To address the aforementioned problems, in a first aspect, the present invention provides a method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel materials, comprising: A nitrate solution containing Fe, Co, Ni, and Mn is mixed with glycine powder to obtain a precursor solution. The precursor solution was heated on a heating platform. After the solvent was evaporated, self-propagating combustion occurred to obtain the precursor powder. The precursor powder was placed in a quartz boat and compacted into a preform; The preform was subjected to high-temperature reduction in a tube furnace purged with Ar / H2 mixed gas. After cooling to room temperature, Mn-doped FeCoNi-based medium-entropy alloy aerogel material was obtained.
[0006] Optionally, nitrates containing Fe, Co, Ni, and Mn are weighed according to stoichiometric ratios and dissolved in deionized water to prepare a nitrate solution, wherein the concentration of total metal ions in the nitrate solution is 0.1 mol / L to 0.9 mol / L.
[0007] Optionally, the nitrate includes nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate.
[0008] Optionally, the percentage content of Fe, Co, Ni and Mn atoms in the nitrate solution is as follows: (Fe5Co3Ni2):Mn=(1-x):x, where x ranges from 0.01 to 0.4, and Fe5Co3Ni2 indicates that the percentage content of Fe, Co and Ni atoms is Fe:Co:Ni=5:3:2.
[0009] Optionally, the molar ratio of glycine to total metal ions is 0.1 to 0.9.
[0010] Optionally, the nitrate solution and glycine powder are mixed uniformly for 30 min to 240 min at a mixing temperature of 10 °C to 90 °C.
[0011] Optionally, the heating temperature of the heating table is 120℃~300℃.
[0012] Optionally, the high-temperature reduction temperature in the tubular furnace is 400℃~900℃, the heating rate is 2℃ / min~10℃ / min, and the reduction time is 2h~8h.
[0013] Secondly, the present invention also provides a Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, which is prepared by the preparation method described above.
[0014] Thirdly, this invention provides an application of Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, specifically its application in the field of electromagnetic wave absorption.
[0015] This invention provides a Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, its preparation method, and its applications. Compared with existing technologies, it has the following advantages: 1. The aerogel material prepared in this invention forms a porous structure through the self-propagating combustion process of glycine. During high-temperature reduction, alloy nanoparticles are interconnected by van der Waals forces to form a three-dimensional network structure, resulting in a lightweight medium-entropy alloy aerogel. Furthermore, Mn doping is used to precisely control the electromagnetic parameters and optimize impedance matching of the medium-entropy alloy aerogel material. 2. The iron-cobalt-nickel based medium-entropy alloy after Mn doping has excellent magnetic loss. Combined with the three-dimensional conductive network and porous structure of the aerogel, it enhances the multiple reflections and scattering of electromagnetic waves, thus making the final medium-entropy alloy aerogel material lightweight and efficient electromagnetic wave absorption performance. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 The images show the three-dimensional and two-dimensional contour plots of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material prepared in Example 1 of this invention at different thicknesses.
[0018] Figure 2 The images show the three-dimensional and two-dimensional contour plots of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material prepared in Example 2 of this invention at different thicknesses.
[0019] Figure 3 The images show the three-dimensional and two-dimensional contour plots of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material prepared in Example 3 of this invention at different thicknesses.
[0020] Figure 4 The image shows the XRD pattern of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel prepared in Example 3 of this invention.
[0021] Figure 5 This is a SEM image of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel prepared in Example 3 of the present invention.
[0022] Figure 6 The electromagnetic parameter distribution diagram is shown for the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel prepared in Example 3 of this invention.
[0023] Figure 7 The images show the three-dimensional and two-dimensional contour plots of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material prepared in Example 4 of this invention at different thicknesses. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application are described clearly and completely. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0025] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.
[0026] This application provides a method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel materials, comprising: Step 1: Mix the nitrate solution containing Fe, Co, Ni, and Mn with glycine powder to obtain a precursor solution.
[0027] Step 2: Place the precursor solution on a heating platform and heat it. After the solvent evaporates, self-propagating combustion occurs to obtain precursor powder.
[0028] Step 3: Place the precursor powder into a quartz boat and compact it into a preform.
[0029] Step 4: The preform is subjected to high-temperature reduction in a tube furnace with Ar / H2 mixed gas. After cooling to room temperature, Mn-doped FeCoNi-based medium-entropy alloy aerogel material is obtained.
[0030] By adjusting the amount of manganese source, medium-entropy alloy aerogel materials with different Mn doping contents can be obtained. The aerogel material is a three-dimensional porous network structure formed by the interconnection of uniform alloy nanoparticles, where manganese is doped into an iron-cobalt-nickel based medium-entropy alloy.
[0031] In step 1, nitrates containing Fe, Co, Ni, and Mn are weighed according to stoichiometric ratios and dissolved in deionized water to prepare a nitrate solution, wherein the concentration of total metal ions in the nitrate solution is 0.1 mol / L to 0.9 mol / L. The nitrates include nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate. The percentage content of Fe, Co, Ni, and Mn atoms in the nitrate solution is: (Fe5Co3Ni2):Mn=(1-x):x, where x ranges from 0.01 to 0.4, and Fe5Co3Ni2 represents the percentage content of Fe, Co, and Ni atoms as Fe:Co:Ni=5:3:2.
[0032] The molar ratio of glycine to total metal ions is 0.1~0.9. The nitrate solution and glycine powder are mixed uniformly for 30min~240min at a temperature of 10℃~90℃.
[0033] In step 2, the heating temperature of the heating platform is 120℃~300℃.
[0034] In step 4, the high-temperature reduction temperature in the tube furnace is 400℃~900℃, the heating rate is 2℃ / min~10℃ / min, and the reduction time is 2h~8h.
[0035] This application describes the preparation of a Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material for electromagnetic wave absorption. This material is created by doping a manganese-containing iron-cobalt-nickel alloy with uniform alloy nanoparticles to form a three-dimensional porous network structure. The main mechanism involves the combined effect of the magnetic loss of the medium-entropy alloy and the dielectric loss of the aerogel's three-dimensional conductive network structure, which promotes the conversion of electromagnetic wave energy into thermal energy, thus achieving efficient absorption of electromagnetic waves.
[0036] The following detailed description uses specific examples.
[0037] Example 1 Step 1: Nitrate solutions were prepared by dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate in deionized water. The masses of the four nitrates were 2.9079 g, 1.7462 g, 1.616 g, and 0 g, respectively. These solutions were then mixed thoroughly with 0.9 g of glycine powder to obtain the precursor solution. The mixing time and temperature were 45 min and 25℃, respectively.
[0038] Step 2: Place the precursor solution on a heating platform and heat it at 200°C. After the solvent evaporates, self-propagating combustion occurs to obtain precursor powder.
[0039] Step 3: Place the precursor powder into a quartz boat and compact it into a preform.
[0040] Step 4: The preform is subjected to high-temperature reduction in a tube furnace with Ar / H2 mixed gas. The high-temperature reduction temperature is 450℃, the heating rate is 5℃ / min, and the reaction lasts for 5 h. After that, the temperature is cooled to room temperature to obtain Mn-doped FeCoNi-based medium-entropy alloy aerogel material.
[0041] Figure 1 (a) and Figure 1 (b) shows the three-dimensional and two-dimensional contour plots of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material at different thicknesses obtained in this embodiment, indicating that the minimum reflection loss (RL) is -11.35 dB and the effective absorption bandwidth (EAB) is 0.255 GHz.
[0042] Example 2 The steps in this embodiment are the same as in embodiment 1, except that the amount of raw materials added is different.
[0043] Step 1: A nitrate solution was prepared by dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate in deionized water. The masses of the four nitrates were 2.8759 g, 1.7270 g, 1.5982 g, and 0.0552 g, respectively. This solution was then mixed thoroughly with 0.9008 g of glycine powder to obtain the precursor solution. The mixing time and temperature were 45 min and 25℃, respectively.
[0044] Step 2: Place the precursor solution on a heating platform and heat it at 200°C. After the solvent evaporates, self-propagating combustion occurs to obtain precursor powder.
[0045] Step 3: Place the precursor powder into a quartz boat and compact it into a preform.
[0046] Step 4: The preform is subjected to high-temperature reduction in a tube furnace with Ar / H2 mixed gas. The high-temperature reduction temperature is 450℃, the heating rate is 5℃ / min, and the reaction lasts for 5 h. After that, the temperature is cooled to room temperature to obtain Mn-doped FeCoNi-based medium-entropy alloy aerogel material.
[0047] Figure 2 (c) and Figure 2 In Figure (d), the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material obtained in this embodiment is shown in the three-dimensional plot and two-dimensional contour plot at different thicknesses, indicating that the minimum reflection loss (RL) is -55.78 dB and the effective absorption bandwidth (EAB) is 4.25 GHz.
[0048] Example 3 The steps in this embodiment are the same as in embodiment 1, except that the amount of raw materials added is different.
[0049] Step 1: A nitrate solution was prepared by dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate in deionized water. The masses of the four nitrates were 2.8370 g, 1.7036 g, 1.5766 g, and 0.1224 g, respectively. This solution was then mixed thoroughly with 0.9008 g of glycine powder to obtain the precursor solution. The mixing time and temperature were 45 min and 25℃, respectively.
[0050] Step 2: Place the precursor solution on a heating platform and heat it at 200°C. After the solvent evaporates, self-propagating combustion occurs to obtain precursor powder.
[0051] Step 3: Place the precursor powder into a quartz boat and compact it into a preform.
[0052] Step 4: The preform is subjected to high-temperature reduction in a tube furnace with Ar / H2 mixed gas. The high-temperature reduction temperature is 450℃, the heating rate is 5℃ / min, and the reaction lasts for 5 h. After that, the temperature is cooled to room temperature to obtain Mn-doped FeCoNi-based medium-entropy alloy aerogel material.
[0053] Figure 3 (e) and Figure 3 In Figure (f), the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material obtained in Example 3 at different thicknesses is shown in the three-dimensional plot and two-dimensional contour plot, indicating that the minimum reflection loss (RL) is -82.87dB and the effective absorption bandwidth (EAB) is 4.42 GHz.
[0054] Figure 4 The XRD pattern of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material shown indicates that the sample has a single medium-entropy alloy structure. Figure 5 The SEM image of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material shown in the image indicates that the material has a uniform three-dimensional network pore structure.
[0055] Figure 6 Figures (a) and (b) show the distribution of electromagnetic parameters of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material obtained in this embodiment. Figures (a) and (b) show the distribution of the real part (ε') and imaginary part (ε'') of the dielectric constant in the 2-18 GHz frequency band, respectively. The real part of the dielectric constant is stably maintained between 14 and 17, demonstrating good dielectric energy storage capacity. The imaginary part of the dielectric constant shows a significant loss peak in the high-frequency band (after 16 GHz), highlighting the excellent dielectric loss characteristics of the material. Figures (c) and (d) show the variation trend of the real part (μ') and imaginary part (μ'') of the permeability. The real part of the permeability gradually decreases from about 1.6 to 0.8 with increasing frequency, showing a reasonable frequency response for magnetic energy storage capacity. The imaginary part of the permeability exhibits specific frequency band distribution characteristics, and its magnetic loss performance is highly consistent with the material design goals and actual application scenarios.
[0056] Example 4 The steps in this embodiment are the same as in embodiment 1, except that the amount of raw materials added is different.
[0057] Step 1: A nitrate solution was prepared by dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate in deionized water. The masses of the four nitrates were 2.7884 g, 1.6744 g, 1.5476 g, and 0.2063 g, respectively. This solution was then mixed thoroughly with 0.9008 g of glycine powder to obtain the precursor solution. The mixing time and temperature were 45 min and 25℃, respectively.
[0058] Step 2: Place the precursor solution on a heating platform and heat it at 200°C. After the solvent evaporates, self-propagating combustion occurs to obtain precursor powder.
[0059] Step 3: Place the precursor powder into a quartz boat and compact it into a preform.
[0060] Step 4: The preform is subjected to high-temperature reduction in a tube furnace with Ar / H2 mixed gas. The high-temperature reduction temperature is 450℃, the heating rate is 5℃ / min, and the reaction lasts for 5 h. After that, the temperature is cooled to room temperature to obtain Mn-doped FeCoNi-based medium-entropy alloy aerogel material.
[0061] Figure 7 (g) and Figure 7 (h) in the figure represents the three-dimensional plot and two-dimensional contour plot of the minimum reflection loss of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material obtained in this embodiment at different thicknesses, showing that the minimum reflection loss (RL) is -23.48dB and the effective absorption bandwidth (EAB) is 3.995 GHz.
[0062] The minimum reflection loss (RL) of Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel materials in Examples 1-4 was investigated. min ) and Effective Absorption Bandwidth (EAB) max Comparative analysis shows that the RL in Example 1 min -11.35 dB, EAB max The RL in Examples 2 and 3 is 0.255 GHz. min The EAB was improved to -55.78 dB and -82.87 dB respectively. max Extended to 4.25 GHz and 4.42 GHz, RL in Example 4 min -23.48 dB, EAB max The wavelength was 3.995 GHz. This indicates that, through Mn doping and structural modulation, the microwave absorption performance of this material was significantly optimized, greatly enhancing its absorption capacity (RL). min The absolute value is significantly improved, and the effective absorption bandwidth is significantly broadened, which effectively solves the problem of insufficient microwave absorption performance of existing iron-based alloys in the background technology, and provides strong support for the development of high-performance microwave absorbing materials.
[0063] 1. The aerogel material prepared in this invention uses glycine as an auxiliary agent, forming a porous structure through the self-propagating combustion process of glycine. During the high-temperature reduction process, the alloy nanoparticles are interconnected by van der Waals forces, forming a three-dimensional network structure to obtain a lightweight medium-entropy alloy aerogel. The preparation method is simple and easy to implement. Furthermore, by doping with Mn, the electromagnetic parameters of the medium-entropy alloy aerogel material can be precisely controlled and impedance matching optimized, achieving effective absorption of electromagnetic waves at low matching thicknesses. By adjusting the matching thickness, efficient absorption of low-frequency electromagnetic waves can also be achieved.
[0064] 2. The iron-cobalt-nickel-based medium-entropy alloy, after Mn doping, exhibits excellent magnetic loss. Combined with the three-dimensional conductive network and porous structure of the aerogel, it enhances the multiple reflections and scattering of electromagnetic waves, resulting in a lightweight and highly efficient medium-entropy alloy aerogel material. This material has low density, solving the problem of traditional alloy absorbing materials being "thick and heavy." The iron-cobalt-nickel-based medium-entropy alloy aerogel of this invention possesses excellent electromagnetic wave absorption performance and is suitable for electromagnetic shielding, radar stealth, and other fields.
[0065] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, characterized in that, include: A nitrate solution containing Fe, Co, Ni, and Mn is mixed with glycine powder to obtain a precursor solution. The precursor solution was heated on a heating platform. After the solvent was evaporated, self-propagating combustion occurred to obtain the precursor powder. The precursor powder was placed in a quartz boat and compacted into a preform; The preform was subjected to high-temperature reduction in a tube furnace purged with Ar / H2 mixed gas. After cooling to room temperature, Mn-doped FeCoNi-based medium-entropy alloy aerogel material was obtained.
2. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 1, characterized in that, Nitrates containing Fe, Co, Ni, and Mn are weighed according to stoichiometric ratios and dissolved in deionized water to prepare a nitrate solution, wherein the concentration of total metal ions in the nitrate solution is 0.1 mol / L to 0.9 mol / L.
3. The preparation method of Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 2, characterized in that, The nitrates include nickel nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate, and manganese nitrate tetrahydrate.
4. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 2, characterized in that, The percentage content of Fe, Co, Ni and Mn atoms in the nitrate solution is as follows: (Fe5Co3Ni2):Mn=(1-x):x, where x ranges from 0.01 to 0.
4. Fe5Co3Ni2 indicates that the percentage content of Fe, Co and Ni atoms is Fe:Co:Ni=5:3:
2.
5. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 2, characterized in that, The molar ratio of glycine to total metal ions is 0.1 to 0.
9.
6. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 1, characterized in that, The nitrate solution and glycine powder are mixed uniformly for 30 min to 240 min at a temperature of 10 °C to 90 °C.
7. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 1, characterized in that, The heating temperature of the heating platform is 120℃~300℃.
8. The method for preparing Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 1, characterized in that, The high-temperature reduction temperature in the tubular furnace is 400℃~900℃, the heating rate is 2℃ / min~10℃ / min, and the reduction time is 2h~8h.
9. A Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.
10. An application of a Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material, characterized in that, The application of the Mn-doped iron-cobalt-nickel-based medium-entropy alloy aerogel material as described in claim 9 in the field of electromagnetic wave absorption.